The Origin of Tribal Development: Colonial Administration and Tribal Development in British India (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The system of administration especially of tribal areas during the British regime can be described as paternalistic in mode and depended largely on the personal qualities of the administrator, his character, initiative and vigour. Military officers were preferred to civilian officers for administering the tribal areas which were known as non-Regulation Provinces. This was not only because of their efficiency but also due to their capacity to suppress the unrest or tribal rebellion if required. Blunt who had experience of tribal administration of civil justice in Arracan in 1828 and later became a member of the Governor General’s Council was followed by Wilkinson and Dent who worked as special commissioners for suppressing the Great Kole Rising of 1832. Wilkinson had direct experience of running administration in the tribal areas of Nagpur for more than a decade and was influenced with the ideals of administration of relief. In Chota-Nagpur during 1834 when Wilkinson’s rules were promulgated and even during 1855 when a separate Santhal Parganas District under the Yule Regulation was created the British policy for these non-Regulation Areas still remained isolationistic in nature.